2018
DOI: 10.1021/acs.biochem.8b00766
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hexamerization, Assembly, and Excluded Strand Specificity for the Sulfolobus solfataricus MCM Helicase

Abstract: A growing body of evidence supports a steric exclusion and wrapping model for DNA unwinding in which hexameric helicases interact with the excluded single-stranded DNA (ssDNA) in addition to the encircled strand. Interactions with the excluded ssDNA have been shown to be mediated primarily by electrostatic interactions, but base stacking with surface-exposed tyrosine residues is an alternative hypothesis. Here, we mutated several external tyrosine and positively charged residues from full-length Sulfolobus sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previously, multiple reports have shown that the fraction unwound by Sso MCM generally hovers between 0.3 and 0.5 depending on the substrate and conditions (Barry et al, 2007; Graham et al, 2011; Graham et al, 2018). The proportion of Sso MCM bound in a productive orientation and state can be determined in a single-turnover DNA unwinding experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, multiple reports have shown that the fraction unwound by Sso MCM generally hovers between 0.3 and 0.5 depending on the substrate and conditions (Barry et al, 2007; Graham et al, 2011; Graham et al, 2018). The proportion of Sso MCM bound in a productive orientation and state can be determined in a single-turnover DNA unwinding experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, cryo-EM structures have shown that dsDNA can enter far into the N-terminal region of CMG before it splits into separated strands and that loops in this region seem to divert the displaced strand to a possible exit tunnel between Mcm3 and Mcm5 (Yuan et al 2020). As with SF-IV helicases, it has been suggested that the exterior surface of MCM helicases may associate with the excluded strand, an interaction that has been proposed to prevent backsliding (Rothenberg et al 2007;Costa et al 2008;Graham et al 2011Graham et al , 2016Graham et al , 2018. However, structural studies of eukaryotic replisome components suggest that the Pol a-primase complex sits close to the N-terminal (fork-proximal) tier of CMG through an interaction with the Ctf4/AND-1 scaffolding protein (Zhu et al 2007;Simon et al 2014;Sun et al 2015b;Georgescu et al 2017;Yuan et al 2019).…”
Section: Unwinding and Step Sizementioning
confidence: 99%